2019
DOI: 10.1063/1.5098515
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wideband and wide-angle polarization rotator based on double W-shaped metasurface

Abstract: In this work, we design a novel polarization converter based on a metasurface with double w-shaped unit cells. The proposed polarization converter can convert linearly polarized incident waves into its cross polarized reflective counterparts in a very wide band with high efficiency. Theoretical analysis and simulation results show that the proposed polarization converter can achieve a 90° polarization rotation, while the polarization conversion ratio (PCR) is above 90% in the frequency range from 8.44 GHz to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In recent years, polarization converters operating in the reflection mode with versatile polarization conversion operations such as from circular to circular, linear to circular, and linear to linear have received great attention. [11][12][13][14][15][16] These converters can be constructed by various resonators including W shape, [17] U shape, [18] L shape, [19,20] H shape, [21] V shape, [22] and split ring with center disc. [23] By designing resonance peaks of these converters sequentially positioned in a frequency band, it is possible to implement a broadband polarization converter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, polarization converters operating in the reflection mode with versatile polarization conversion operations such as from circular to circular, linear to circular, and linear to linear have received great attention. [11][12][13][14][15][16] These converters can be constructed by various resonators including W shape, [17] U shape, [18] L shape, [19,20] H shape, [21] V shape, [22] and split ring with center disc. [23] By designing resonance peaks of these converters sequentially positioned in a frequency band, it is possible to implement a broadband polarization converter.…”
Section: Introductionmentioning
confidence: 99%
“…Although these polarization converters have broadband and high polarization conversion rate (PCR), their bandwidths decrease as the incidence angle increases. [17,[21][22][23] Therefore, they are sensitive to the incidence angle.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, it has been found that metasurface can provide a convenient way to control the polarization state of EM wave. In recent years, to update the conventional design method, many different types of polarization converters have been proposed based on various anisotropic or chiral metasurfaces, which can perform different polarization conversions, such as cross polarization conversion [3][4][5][6][7][8][9][10] or linear-to-circular polarization conversion [11][12][13][14][15][16][17] . In addition, A righthanded/left-handed circularly polarized (RCP/ LCP) wave will be converted to a LCP/ RCP one after reflection on a conducting surface, however, based on a proper anisotropic or chiral metasurface, a CP-maintaining metasurface can be proposed, which can keep the handedness of the reflected wave the same as that of the CP incident one.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the linear‐to‐linear, linear‐to‐circular, and circular‐to‐circular polarization based on metasurface has been obtained 14–17 . For example, a pair of V‐shaped metasurface structures, 18 I‐shaped structures, 19 cut wire shaped, 20 double‐W‐shaped, 21 double split ring, 22 L‐patterns 23 have also been published. In addition, Xiaojun Huang 24 designed a composite structure metasurface consists of metal strip and rectangular ring.…”
Section: Introductionmentioning
confidence: 99%